COMPARISON OF INTRAOPERATIVE TIME, WOUND INFECTION AND SEROMA FORMATION IN PATIENTS UNDERGOING SUBLAY VERSUS ONLAY MESH HERNIOPLASTY FOR VENTRAL HERNIA (The Research of Medical Science Review, 2025)
Objective: To compare the outcome of sublay versus onlay mesh hernioplasty for primary ventral hernia in terms of frequency of seroma formation, wound infection and mean operative time. Methodology: This randomized controlled trial was conducted at North Surgical Ward, King Edward Medical University/Mayo Hospital, Lahore, over six months. A total of 140 patients aged 18–60 years with primary ventral hernia were randomly assigned to undergo either sublay (n=70) or onlay (n=70) mesh repair. Patients with obesity, strangulated hernia, or comorbidities affecting wound healing were excluded. Postoperative outcomes including seroma formation (assessed by ultrasound), wound infection (graded via Southampton system), and operative time were compared. Results: Seroma formation occurred in 2.9% of sublay cases versus 17.1% in onlay (p = 0.005). Wound infections were observed in 7.1% of sublay and 17.1% of onlay patients (p = 0.070). Mean operative time was significantly longer in the sublay group (82.24 ± 7.30 minutes) compared to the onlay group (73.70 ± 7.38 minutes) (p < 0.001). Stratified analysis revealed significantly fewer seromas and infections among sublay patients across most subgroups. Conclusion: Sublay mesh hernioplasty is associated with significantly reduced seroma formation and a trend toward fewer wound infections compared to onlay repair, albeit with longer operative time. These findings support the use of sublay technique for safer postoperative outcomes.